Tafsir Maudhu'i dalam Persepektif Akademik Kerangka Teoretis dan Aplikasi Praktis - Aulia Umami; Windi Shafira; Zulham Lutfi Tambunan; Rozian Karnedi (UIN Fatmawati Sukarno Bengkulu, 2025)
As a holy book, the Qur'an functions as a law and guideline for the lives of Muslims. In this context, Muslims in modern times often have difficulty in understanding the contents of the Qur'an as a whole. Therefore, experts in interpretation then formulated a method of understanding the Qur'an according to certain themes or what is called the Maudlu'i interpretation method. This article aims to describe the Maudlu'i interpretation, the problems of Maudlu'i interpretation, and examples of Maudlu'i interpretation. This literature review was conducted using a qualitative descriptive method. The results of the study indicate that the Maudlu'i interpretation is an interpretation method that attempts to explain the contents of the Qur'an based on certain themes. The interpretation methods that developed in the 20th century are divided into 3 categories, namely maudlu'i interpretation which focuses on terminology, maudlu'i interpretation which focuses on themes or topics in the Qur'an, and maudlu'i interpretation which focuses on a particular letter in the Qur'an. Regardless of the dynamics of its advantages and disadvantages, Maudlu'i interpretation is more appropriate to the living conditions of modern Muslims. The results of the study concluded that the Maudlu'i interpretation method has an important role in understanding the contents of the Qur'an.